Agriculture et projet urbain durables en périurbain : la nécessité d’un réel changement de paradigme - Christian Peltier (Éditions en environnement VertigO, 2010)
City dwellers are looking for nature, inside town and near it. French Agriculture Chambers and urban areas are reflecting upon agriculture space in those areas. More than a necessary territorial dialogue between all of the present actors, it’s the question of the territorial sustainability planning which is asked… and ancient logics cutting spaces in urbanised spaces and open spaces can’t be used now. Actors ought to build a common world ! This means, at first, a real sustainability diagnostic on agricultural and urban ac-tivities, base of all common and stand project, and a real education for a sustainable territorial development beyond an environmental education. With those two conditions, all the actors can build a common culture. In this article, we try to measure how “dialogic de-mocracy” and “education for territorial sustainable development” is going, or not, to concrete in a few places observed in the West of France. Two mains situations appear.